2016
DOI: 10.1111/let.12130
|View full text |Cite
|
Sign up to set email alerts
|

Durophagous predation on scaphitid ammonoids in the Late Cretaceous Western Interior Seaway of North America

Abstract: This study is the first to report a trend of predation intensity on scaphitid ammonoids from the Turonian to the Maastrichtian (Late Cretaceous) on the basis of analysis of ventral shell breakage in large samples from the US Western Interior Province. Analysis of 835 adult specimens revealed ventral shell breakage in 50 specimens. In most of the damaged specimens, the breakage occurred in a preferred position at the rear part of the body chamber. Ventral breakage is rare in the Turonian specimens, whereas it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Predation indicators, such as healed injuries, are present on 5% of scaphite specimens (Fig. 1); a similar incidence of predation as observed in other scaphite accumulations interpreted as in situ (21). Although it is more challenging to determine sex in baculites than in scaphites, for those baculite specimens where this assignment could be made, the proportion of males and females is equal.…”
Section: Resultsmentioning
confidence: 83%
“…Predation indicators, such as healed injuries, are present on 5% of scaphite specimens (Fig. 1); a similar incidence of predation as observed in other scaphite accumulations interpreted as in situ (21). Although it is more challenging to determine sex in baculites than in scaphites, for those baculite specimens where this assignment could be made, the proportion of males and females is equal.…”
Section: Resultsmentioning
confidence: 83%
“…Radwański (1996) documented paired punctures that pierced the shells of latest Maastrichtian scaphitid ammonites and interpreted them as having been produced by predatory crabs. Similar traces of damage on scaphitids are not uncommon in the Upper Cretaceous of North America (Takeda et al, 2016). Externally inflicted injuries, indicated by repaired damage on mature shells, account for an average incidence of 10 per cent in Maastrichtian scaphitids from North America,…”
Section: Raninoidian Crabsmentioning
confidence: 72%
“…Similar to other Conchiferans, the outer shells of Cephalopods are thought to also function by protecting their soft parts against predators. Shell morphological studies have indicated that outer shell breakages caused by fatal and nonfatal predatory attacks were often found in various extant Nautilus (e.g., Tanabe, 1988) and extinct, shelled cephalopod fossils (e.g., Takeda and Tanabe, 2015; Takeda et al, 2016). Moreover, members of Cephalopods had developed swimming ability, which had assisted their radiation both horizontally and vertically in the ocean habitat, in contrast to the rest of the marine Mollusks, which are mostly benthic.…”
Section: Discussionmentioning
confidence: 99%